Meningkatkan Kemampuan Berbahasa Anak Usia Dini Melalui Lagu - Hesti Nova Arlinda; Hanifah Nurul Azizah; Eva Atitawati; Ali Iskandar Zulkarnain (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to improve children's language skills through songs, thereby providing children with an understanding of the importance of language development. Language development in children focuses on experiences and interactions with the environment. Language, as defined by Santrock, is a system of symbols for communication. Improving children's language skills, particularly vocabulary, can be achieved through engaging learning. One effective method is using children's songs. Children's songs are a useful tool for language learning because they can enrich new vocabulary and help children communicate better. Children's songs can also increase creativity, self-confidence, and foster a positive attitude in children. This study used a literature review method (library research) to analyze scientific literature, such as journals and relevant articles, to examine the effect of language learning through children's songs on early childhood vocabulary development.